دور الوعي البيئي في تحقيق ممارسات التجهيز العكسي دراسة تحليلة لاراء عينة من العاملين في شركة كرونجي للمشروبات الغازية – كركوك / العراق - درويش, أ.م.د. رعد الياس (Sulaimani Journal for Humanities, 2023)
The research seeks to test the role of environmental awareness through its dimensions (emotional, intellectual, behavioral) in achieving reverse logistics practices (recycling, reuse, remanufacturing, renewal) by analyzing the responses of a sample of 50 individuals working in the Al-Karwanji Production Company. Juices - Kirkuk / Iraq, by adopting the descriptive analytical approach and adopting the research statistical package analysis program SPSS V. 26. The results of the research indicated that environmental awareness is linked to a strong relationship with reverse logistic practices. Environmental awareness also has a major impact on achieving reverse logistics practices. The research provided a set of recommendations. The most important of which was working to increase the involvement of workers in training courses to raise the level of knowledge they have about the dangers of environmental pollution, in addition to the benefits resulting from rationalizing energy consumption and available natural resources.
Keywords: environmental awareness; reverse processing practices